A avaliação da efetividade da política de ressarcimento ao Sistema Único de Saúde - Freitas, Marcella Abunahman (2011)
The need to restrain the lack of control of the health plan market became an important issue in the national scene in the 90s. Thus, 10 years after the Unified Health System's (SUS) creation, in a context of pressure and of low health plan regulation, the Law nº 9.656/1998 was instituted. It was an unprecedented legislation in Brazil because it regulated the activities of health service companies (OPS) at national level. Among other issues, the Law established the SUS reimbursement policy, imposing in the Article nº 32 that when a beneficiary uses the public system for a procedure which is covered by his or her health plan, the OPS should reimburse the SUS. However, this policy is one of the conflicts that lie within the limits of interests between the private and public sector: already in 1998 OPSs filed an unconstitutional act against the policy and they resort to lawsuits for not paying the public coffers. Even after 12 years of the Law's creation, it is still unknown the real impact of Article nº 32 on its target public, therefore, this study aimed to evaluate the effectiveness of the SUS reimbursement policy. The methodology used was based on the evaluation of data managed by the Supplementary Health National Agency (ANS) and the Ministry of Health / DATASUS, and of interviews performed with managers of the public and the private sector. Despite ANS’s efforts, the results showed reduced effectiveness of the policy in financial and legal terms; and on its target public. Only 22% of what ANS charged returned to the Unified System from 1999 to 2006, the policy is viewed as unconstitutional by the market and has little impact over OPSs, SUS and beneficiaries. Issues such as the values of the national unified equivalence procedure table (TUNEP), the reimbursement’s unconstitutionality and the beneficiary’s own option to use SUS’s services were voiced by health plan managers as factors that generate OPSs’s resistance towards the policy. Public actors affirmed its importance for beneficiary and SUS protection, and the fact that made possible the construction of the Registry of Beneficiaries of all OPSs. On the other hand, they recognize the policy’s poor results. It is recommended to maintain the SUS reimbursement policy as a tool to deter companies which have the intention to bypass the legal requirements of the Regulatory Agency, that acts promoting the public interest in supplementary health care. However, it must undergo the necessary reformulations and consensus must be established between the Unified System and the supplementary sector.